An Assistive Device for Direction Estimation of a Sound Source. - Kim, Ki-Won; Choi, Jung-Woo; Kim, Yang-Hann (Assistive Technology)
A wearable assistive device is proposed that visually indicates the direction of a sound source for people who cannot hear but can see when a loud sound occurs. The device has been implemented in the shape of common eyeglasses, so that it does not draw attention to the wearer's hearing impairment. Acoustical information is acquired by an array of microelectromechanical-system microphones attached to the eyeglasses. The direction of a sound source is estimated in real time and indicated to the user via four light-emitting diodes designating the front, back, left, and right directions. Two methods for estimating the sound direction were compared: delay-and-sum beamformer and sound pressure level (SPL) comparison. The performance of the directional estimation was evaluated using the head-and-torso simulator. The SPL comparison method was 92% accurate versus the 84% accuracy of the delay-and-sum beamformer approach.